2015
DOI: 10.4238/2015.august.19.1
|View full text |Cite
|
Sign up to set email alerts
|

Potential of berberine to enhance antimicrobial activity of commonly used antibiotics for dairy cow mastitis caused by multiple drug-resistant Staphylococcus epidermidis infection

Abstract: ABSTRACT. Berberine is a plant alkaloid with antimicrobial activity against a variety of microorganisms. In this study, the antimicrobial properties of berberine against multi-drug resistant field isolates of Staphylococcus epidermidis were investigated using berberine alone or in combination with a commonly used antibiotics in veterinary clinics, including penicillin, lincomycin, and amoxicillin. The results indicated that the minimum inhibitory concentrations of berberine, penicillin, lincomycin, and amoxici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 26 publications
1
13
0
Order By: Relevance
“…This infers that although berberine displays excellent inhibiting effects against S. aureus while used alone berberine is not sufficient to control S. aureus infections. Therefore, we suggest that berberine be used as an ancillary drug in combination with other antibiotics in S. aureus related PJI control, since berberine shows remarkable synergy effects with a wide range of antibiotics [27, 29, 58, 59]. For example, a study by Zuo et al revealed that berberine significantly lowered the MIC values of a series of antibiotics against S. aureus including MRSA [59].…”
Section: Discussionmentioning
confidence: 99%
“…This infers that although berberine displays excellent inhibiting effects against S. aureus while used alone berberine is not sufficient to control S. aureus infections. Therefore, we suggest that berberine be used as an ancillary drug in combination with other antibiotics in S. aureus related PJI control, since berberine shows remarkable synergy effects with a wide range of antibiotics [27, 29, 58, 59]. For example, a study by Zuo et al revealed that berberine significantly lowered the MIC values of a series of antibiotics against S. aureus including MRSA [59].…”
Section: Discussionmentioning
confidence: 99%
“…Three alkaloids were clearly defined as druggable structures: berberine, platensymicin, platencin (see Tables 1 and 2) . These three alkaloids showed stronger adjuvant potency with a more specific effect than the set of flavonoids tested 33,[46][47][48] , the latter two are being considered to be antibiotics per se and are under further development by Merck pharmaceuticals 48 (see Table 2). The mechanism of action of these three compounds has been proposed to be orthogonal to those of the CADs.…”
Section: Summary Of the Literature Review Resultsmentioning
confidence: 99%
“…The mechanism of action of these three compounds has been proposed to be orthogonal to those of the CADs. Further functionalization of their alkaloidal skeletons may allow improvement of their medicinal chemistry 33,[46][47][48] .…”
Section: Summary Of the Literature Review Resultsmentioning
confidence: 99%
See 2 more Smart Citations